ERS/ESTS/ESTRO/ESR/ESTI/EFOMP statement on management of incidental findings from low dose CT screening for lung cancer - O'Dowd, Emma; Tietzova, Ilona; Bartlett, Emily; Devaraj, Anand; Biederer, Jürgen; Brambilla, Marco; Brunelli, Alessandro; Chorostowska-Wynimko, Joanna; Decaluwe, Herbert; Ruysscher, Dirk De; Wever, Walter De; Donoghue, Matthew; et al. (The European respiratory journal, 2023)
Background Screening for lung cancer with low radiation dose computed tomography has a strong evidence base, is being introduced in several European countries and is recommended as a new targeted cancer screening programme. The imperative now is to ensure that implementation follows an evidence-based process that will ensure clinical and cost effectiveness. This European Respiratory Society (ERS) task force was formed to provide an expert consensus for the management of incidental findings which can be adapted and followed during implementation. - Methods A multi-European society collaborative group was convened. 23 topics were identified, primarily from an ERS statement on lung cancer screening, and a systematic review of the literature was conducted according to ERS standards. Initial review of abstracts was completed and full text was provided to members of the group for each topic. Sections were edited and the final document approved by all members and the ERS Science Council. - Results Nine topics considered most important and frequent were reviewed as standalone topics (interstitial lung abnormalities, emphysema, bronchiectasis, consolidation, coronary calcification, aortic valve disease, mediastinal mass, mediastinal lymph nodes and thyroid abnormalities). Other topics considered of lower importance or infrequent were grouped into generic categories, suitable for general statements. - Conclusions This European collaborative group has produced an incidental findings statement that can be followed during lung cancer screening. It will ensure that an evidence-based approach is used for reporting and managing incidental findings, which will mean that harms are minimised and any programme is as cost-effective as possible. - Tweetable abstract ERSpublications - click to tweetLung cancer screening with low radiation dose computed tomography commonly detects incidental findings. This collaborative statement reviews the evidence and how this informs a clinically effective approach to these findings. https://bit.ly/3qlrlD3
Gesehen am 24.05.2024